Prevalence and Pattern of Dietary Supplements Use among Female Medical Students: A Bangladesh Study (Journal of Brahmanbaria Medical College, 2026)
Background: Over the years, Bangladesh has been experiencing substantial transformation in demographic, health and nutritional status of the population. Although malnutrition rates among children and women have reduced, micronutrient deficiencies are still present. Research evidence suggests a higher proportion of supplement consumption among females, younger age group. As there is extensive feminization of medical education in Bangladesh is going on, it was interesting to explore the prevalence and associated factors of Dietary Supplements (DS) use among them. To analyze the prevalence and pattern of DS use among the female medical students of Bangladesh. Materials and methods: This descriptive cross-sectional study was conducted in the Department of Pharmacology & Therapeutics of 18 Medical Colleges of Bangladesh including both government and nongovernment institutions from May 2024 to October 2024. A structurred questionnaire survey was conducted among the 3rd year and 4th year MBBS students of studied medical colleges who agreed to participate the study, and a total of 1688 medical students participated in this study. Results: The overall prevalence of DS use was 41.00% and 48.27% respondents use at least 1 type of supplement. The most consumed DS were multivitamins-minerals combination (25.15%) followed by vitamin C (24.87%) iron (22.26%) vitamin D (19.37%) and calcium (18.21%) respectively. The most common reason for taking DS was for improvement of overall health (38.58%). DS was taken asself-medication among 46.24% of respondents. Supplement intake was significantly associated with types of medical colleges (p =0.00008) and marital status (p value = 0.007*). Conclusion: The proportion and pattern of supplement consumption among study population were comparable to previous studies. It would be commendable to review the undergraduate curriculum in regards of DS for encouraging rational prescribing of supplements in upcoming days.JBRMC, Volume 08 Issue 01 January 2026 ; 25-31